Visible light triggered synthesis of spiro[indoline-3,4′-quinoline] via oxidative coupling of indole with enaminone and malononitrile - Maury S.K.; Kushwaha A.K.; Kamal A.; Singh H.K.; Singh S. (My University, 2025)
In the most recent research, a straightforward, effective, and environmentally friendly method for producing spiro[indoline-3,4′-quinoline] was developed in ethanol using a photocatalyst eosin y and a 22 W LED lamp. This method involves the oxidative coupling of indole with enaminone and malononitrile. This method's key features include the absence of metals, low cost, environmental friendliness, greenness, non-toxicity, ease of handling, and use of renewable energy like visible light. This method exhibits a wide substrate scope for indole and active methylene compounds, including different enaminones. For the first time, spiro compounds were produced using visible light-mediated metal-free multicomponent synthesis under benign reaction conditions. © 2022